Nano-in-Micro-Particles Consisting of PLGA Nanoparticles Embedded in Chitosan Microparticles via Spray-Drying Enhances Their Uptake in the Olfactory Mucosa - Spindler, Lena Marie; Feuerhake, Andreas; Ladel, Simone; Günday, Cemre; Flamm, Johannes; Günday-Türeli, Nazende; Türeli, Emre; Tovar, Günter E. M.; Schindowski, Katharina; Gruber-Traub, Carmen (Frontiers in Pharmacology, 2021)
Intranasal delivery has gained prominence since 1990, when the olfactory mucosa was recognized as the window to the brain and the central nervous system (CNS); this has enabled the direct site specific targeting of neurological diseases for the first time. Intranasal delivery is a promising route because general limitations, such as the blood-brain barrier (BBB) are circumvented. In the treatment of multiple sclerosis (MS) or Alzheimer’s disease, for example, future treatment prospects include specialized particles as delivery vehicles. In this study, we produced PLGA nanoparticles of different sizes and revealed for the first time their size-time-dependent uptake mechanism into porcine olfactory mucosa. The intracellular uptake was observed for 80 nm and 175 nm within only 5 min after application to the epithelium. After 15 min, even 520 nm particles were detected, associated with nuclei. Especially the presence of only 520 nm particles in neuronal fibers is remarkable, implying transcellular and intracellular transport via the olfactory or the trigeminal nerve to the brain and the CNS. Additionally, we developed successfully specialized Nano-in-Micro (NiMP) particles via spray drying, consisting of PLGA nanoparticles embedded into chitosan microparticles, characterized by high encapsulation efficiencies up to 51 %, reproducible and uniform size distribution, as well as smooth surface. Application of NiMPs accelerated the uptake compared to purely applied PLGA nanoparticles. NiMPs were spread over the whole transverse section of the olfactory mucosa within 15 min. Faster uptake is attributed to additional paracellular transport, which was examined via tight-junction-opening. Furthermore, a separate chitosan penetration gradient of ~150 µm caused by dissociation from PLGA nanoparticles was observed within 15 min in the lamina propria, which was demonstrated to be proportional to an immunoreactivity gradient of CD14. Due to the beneficial properties of the utilized chitosan-derivative, regarding molecular weight (150-300 kDa), degree of deacetylation (80 %), and particle size (0.1-10 µm) we concluded that M2-macrophages herein initiated an anti-inflammatory reaction. In conclusion, we demonstrated the possibility for PLGA nanoparticles, as well as for chitosan NiMPs, to take all three prominent intranasal delivery pathways to the brain and the CNS; namely transcellular, intracellular via neuronal cells, and paracellular transport.